Effects of Salt Thickness on the Structural Deformation of Foreland Fold-and-Thrust Belt in the Kuqa Depression, Tarim Basin: Insights From Discrete Element Models - Li, Changsheng; Yin, Hongwei; Wu, Zhenyun; Zhou, Peng; Wang, Wei; Ren, Rong; Guan, Shuwei; Li, Xiangyun; Luo, Haoyu; Jia, Dong (Frontiers in Earth Science, 2021)
The salt layer is critical for the structural deformation in the salt-bearing fold-and-thrust system, which not only acts as the efficient décollement layer but also flows to form salt tectonics. Kuqa depression has a well preserved thin-skinned fold-and-thrust system with the salt layer as the décollement. To investigate the effects of salt thickness on the structural deformation in the Kuqa depression, three discrete element models with different salt thicknesses were constructed. The experiment without salt was controlled by several basal décollement dominant faults, forming several imbricate sheets. The experiments with salt developed the decoupled deformation with the salt layer as the upper décollement (subsalt, intrasalt, and suprasalt), significantly similar to the Kuqa depression along the northern margin of Tarim Basin. Basal décollement dominant imbricated thrusts formed at the subsalt units, while the monoclinal structure at the suprasalt units. The decoupled deformation was also observed in the tectonic deformation graphics, distortional strain fields, and max shear stress fields. Whereas the salt layer was thickened in the thick salt model, and the salt thickness of the thin salt model varied slightly because the thin salt weakened the flowability of the salt. The lower max shear stress zone was easily formed in the distribution region of salt under the action of compression stress, which is conducive to the flow convergence of salt and the crumpled deformation of interlayer in salt. The results are well consistent with the natural characteristic of structural deformation in the Kuqa depression. Our modeling result concerns the structural characteristics and evolution of salt-related structures, and the effects of salt thickness on the structural deformation in the compressional stress field, which might be helpful for the investigations of salt-related structures in other salt-bearing fold-and-thrust belts.